Zeros for the Gradients of Weakly A-Harmonic Tensors - Yuxia Tong; Jiantao Gu; Shenzhou Zheng (Journal of Applied Mathematics)
The Caccioppoli inequality of weakly A-harmonic tensors has been proved, which can be used to consider the weak reverse Hölder inequality, regularity property, and zeros of weakly A-harmonic tensors.